Firn Evolution at Camp Century, Greenland: 1966–2100 - Vandecrux, Baptiste; Colgan, William; Solgaard, Anne M.; Steffensen, Jørgen Peder; Karlsson, Nanna B. (Frontiers in Earth Science, 2021)
Camp Century is an American military base built in 1959 under the surface of the Greenland ice sheet and decommissioned in 1967. Here, we use outputs from RACMO2.3p2 and CanESM2 climate models, adjusted to meteorological observations, and a firn model to simulate the firn density and temperature at Camp Century between 1966 and 2100. The model output is evaluated against an extensive set of firn 3observations and three Representative Concentration Pathways (RCP2.6, 4.5 and 8.5) are considered as future scenarios. Our model suggests that the upper horizon of the Camp Century debris field – observed at a depth of 32 m in 2017 – will continue to be buried by persistent net accumulation over the next eighty years under all RCP scenarios. This horizon depth will be between 58 and 64 m in 2100, depending on the RCP scenario. We estimate a maximum meltwater percolation depth of 1.1 m under all RCP scenarios. We therefore find it extremely unlikely that surface meltwater interacts with the subsurface debris field at Camp Century before 2100 under all RCP scenarios. Camp Century’s future is representative of the firn area in northwestern Greenland, bound to shift from dry snow to a percolation regime. Our model suggests that 10 m firn temperatures at Camp Century will increase from −24.0°C in 1966 to −21.3, −20.0 and −18.6°C in 2100 under the RCP2.6, 4.5 and 8.5 scenarios, respectively. We reveal a previously unknown warm bias in air temperatures simulated at Camp Century by both RACMO2.3p2 and CanESM2 climate models which needs to be accounted for when using these models to predict melt, firn evolution and sea-level contribution of the Greenland ice sheet. We also present novel in situ measurements of firn compaction rates, which indicate that about 25% of firn compaction of the top 62 m of firn occurs below 20 m depth. This highlights the importance of deep-firn compaction measurements for model evaluation and correction of altimetry products.